Effect of heel construction on muscular control potential of the ankle joint in running - Willwacher, S.; Potthast, W.; Konrad, M.; Brüggemann, G. P. (Journal of Applied Biomechanics, 2013)
The purpose of this study was to investigate the effect of heel construction on ankle joint mechanics during the early stance phase of running. Kinematic and kinetic parameters (ankle joint angles, angular velocities and joint moments, lever arms of ground reaction force, triceps surae muscle tendon unit lengths, and rates of muscle tendon unit length change) were calculated from 19 male subjects running at 3.3 m/s in shoes with different heel constructions. Increasing heel height and posterior wedging amplified initial plantar flexion velocity and range. The potential for a muscle to control the movement of a joint depends upon its ability to produce joint moments. Runners in this study showed decreased external eversion moments and an increase in eversion range. Maximum eversion angles were not significantly affected by shoe conditions. Without considerable tendon prestretch, joint moment generation potentials of triceps surae and deep plantar flexors might be inhibited due to rapid plantar flexion based on the force-velocity relationship. It could be speculated that increasing ankle inversion at heel strike could be a strategy to keep maximum eversion angles inside an adequate range, if joint moment generation potentials of deep plantar flexors are inhibited due to rapid plantar flexion.